Pengaruh Return On Assets, Komisaris Independen, dan Earning Per Share terhadap Harga Saham - Devi Elfrida Sihombing; Lenawati Haryanto (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to determine whether Return on Assets (ROA), Independent Commissioner, and Earning per Share (EPS) have a positive effect on stock prices. The object of the research was conducted at conventional banking sector companies listed on the Indonesia Stock Exchange in 2018 – 2022. The sampling technique used purposive sampling with a total sample of 145 secondary data in the form of annual financial reports processed based on criteria for the period of the financial year which is available on the website www.idx.co.id. The results of research and descriptive statistical tests using stock price calculations at the end of each year's period show that ROA, Independent Commissioner, and EPS simultaneously have a significant effect on tax law. Partially from the independent variable test, the results showed that the ROA variable had a significant positive effect on stock prices with a p-value Sig 0.041 (probability value less than Sig 0.05) and the EPS variable had a significant positive effect on stock prices with a p-value Sig 0.002. Meanwhile, the Independent Commissioner variable has no significant positive effect on stock prices with a p-value of Sig 0.953 (probability value greater than Sig 0.05).